2016
DOI: 10.1093/ntr/ntw009
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents’ and Young Adults’ Knowledge and Beliefs About Constituents in Novel Tobacco Products

Abstract: Introduction: Novel tobacco products, such as little cigars, cigarillos, hookah, and e-cigarettes, and their smoke or aerosol contain chemicals which the FDA has determined to be Harmful or Potentially Harmful Constituents. We explored adolescents' and young adults' knowledge and beliefs about constituents in novel tobacco products and their smoke or aerosol, in order to inform risk communication messages. Methods: Seventy-seven adolescents and young adults (ages 13-25) participated in 10 focus groups, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 19 publications
3
28
0
Order By: Relevance
“…Cross-sectional studies in the US, UK, Australia, Mexico, and Canada using convenience and probability samples have found that the public was most aware that carbon monoxide (48–86%), nicotine (64–94%), and tar (48–86%) are in cigarette smoke (Borland & Hill, 1997; Brewer et al, 2016; Cummings et al, 2004b; Environics Research Group, 1996a, b, 2003a, b; Hammond et al, 2006; Ipsos-Eureka, 2009; Moracco et al, 2016; O'connor et al, 2006; Swayampakala et al, 2015; Wiseman et al, 2016). Fewer people were aware that cyanide (13–72%) and arsenic (6–58%) are in cigarette smoke (Brewer et al, 2016; Cummings et al, 2004b; Environics Research Group, 1996b, 2003b; Hammond et al, 2006; Moracco et al, 2016; Siahpush et al, 2006; Wiseman et al, 2016), and very few people knew that other constituents such as nitrosamines (6–25%), polonium (8–24%), and mercury (11–26%) are in cigarette smoke (Boynton et al, 2016; Brewer et al, 2016; Cummings et al, 2004b; Environics Research Group, 1996b; Siahpush et al, 2006; Swayampakala et al, 2015; Wiseman et al, 2016). One study of pregnant women in Lebanon found that 70% knew cigarette smoke contained addictive substances and carcinogens (Chaaya et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Cross-sectional studies in the US, UK, Australia, Mexico, and Canada using convenience and probability samples have found that the public was most aware that carbon monoxide (48–86%), nicotine (64–94%), and tar (48–86%) are in cigarette smoke (Borland & Hill, 1997; Brewer et al, 2016; Cummings et al, 2004b; Environics Research Group, 1996a, b, 2003a, b; Hammond et al, 2006; Ipsos-Eureka, 2009; Moracco et al, 2016; O'connor et al, 2006; Swayampakala et al, 2015; Wiseman et al, 2016). Fewer people were aware that cyanide (13–72%) and arsenic (6–58%) are in cigarette smoke (Brewer et al, 2016; Cummings et al, 2004b; Environics Research Group, 1996b, 2003b; Hammond et al, 2006; Moracco et al, 2016; Siahpush et al, 2006; Wiseman et al, 2016), and very few people knew that other constituents such as nitrosamines (6–25%), polonium (8–24%), and mercury (11–26%) are in cigarette smoke (Boynton et al, 2016; Brewer et al, 2016; Cummings et al, 2004b; Environics Research Group, 1996b; Siahpush et al, 2006; Swayampakala et al, 2015; Wiseman et al, 2016). One study of pregnant women in Lebanon found that 70% knew cigarette smoke contained addictive substances and carcinogens (Chaaya et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Limiting ad content to such features represents a potential strategy for appealing to adult smokers, who report increased intentions to try e-cigarettes following exposure to instructional and anti-smoking ads, 33 while avoiding appealing to youth. More research is needed, however, as some work suggests that youth also may be interested in learning about the health effects and toxicity of novel tobacco products; 34 in a study by Farrelly et al 13 youth highly rated instructional e-cigarette ads. It may be that because e-cigarettes are a novel device, youth may feel social pressure to know how to use them, making product appeals more persuasive than in ads for more familiar substances like alcohol.…”
Section: Discussionmentioning
confidence: 99%
“…Half of the focus groups focused on hookah (k=5) and the other half focused on LCCs (k=5). Participants also discussed OTP constituents and electronic nicotine delivery systems in all focus groups; those data are reported elsewhere (see Wagoner et al, 2016; Wiseman et al, 2016). At the conclusion of each focus group, we provided participants a handout about the harms of using hookah and LCCs, as well as resources (e.g., website URLs) for quitting tobacco (adapted from the Campaign for Tobacco-Free Kids, American Lung Association, American Cancer Society, and National Cancer Institute).…”
Section: Methodsmentioning
confidence: 99%